Considerations for establishment of a private virtual hospital identified using an implementation science approach - Olivia J. Fisher; Caroline Grogan; Andrew Barron; Shanthi Kanagarajah; Sue-Ellen Smith; Ian Smith; Kelly McGrath (Scientific Reports)
Abstract Virtual hospitals are rapidly being implemented internationally. Research has predominantly focused on clinical outcomes not implementation. We aimed to identify pre-implementation determinants to enable health services to tailor virtual hospital models, increasing likelihood of suitability, acceptability, uptake, clinical effectiveness, and sustainability. We aimed to inform the design and implementation of a private Australian virtual hospital by identifying contextual barriers, enablers, and considerations. We conducted a qualitative pre-implementation determinant study using snowball sampling and semi-structured interviews (n = 37) between February and July 2023 with consumers/carers/both (n = 11), clinicians (doctors/allied health/nursing/personal carers), hospital, health service and aged care leadership (n = 22), and public health stakeholders (n=4). Deductive framework analysis based on the PERCS implementation science framework was used. The following key determinants were identified: Enablers – strong executive leadership support; enthusiasm for expanding rural and remote services; need for a clear vision; strong tension for change; commitment to high-quality healthcare. Major barrier: restrictive funding models that stifle opportunities for innovation. Other barriers: technological limitations; communication challenges; workforce issues; clinicians’ opinions varied on safety and suitability of virtual healthcare. This implementation science approach enabled identification of a broad set of determinants not previously reported, relevant locally and for an international audience. Evaluation of implementation outcomes is necessary.